Chronic Implant-Related Bone Infections—Can Immune Modulation be a Therapeutic Strategy? - Seebach, Elisabeth; Kubatzky, Katharina F. (Frontiers in Immunology, 2019)
Chronic implant-related bone infections are a major problem in orthopedic and trauma-related surgery with severe consequences for the affected patients. As antibiotic resistance increases in general and because most antibiotics have poor effectiveness against biofilm-embedded bacteria in particular, there is a need for alternative and innovative treatment approaches. Recently, the immune system has moved into focus as the key player in infection defense and bone homeostasis, and the targeted modulation of the host response is becoming an emerging field of interest. The aim of this review was to summarize the current knowledge of impaired endogenous defense mechanisms that are unable to prevent chronicity of bone infections associated with a prosthetic or osteosynthetic device. The presence of foreign material adversely affects the immune system by generating a local immune-compromised environment where spontaneous clearance of planktonic bacteria does not take place. Furthermore, the surface structure of the implant facilitates the transition of bacteria from the planktonic to the biofilm stage. Biofilm formation on the implant surface is closely linked to the development of a chronic infection, and a misled adaption of the immune system makes it impossible to effectively eliminate biofilm infections. The interaction between the immune system and bone cells, especially osteoclasts, is extensively studied in the field of osteoimmunology and this crosstalk further aggravates the course of bone infection by shifting bone homeostasis in favor of bone resorption. T cells play a major role in various chronic diseases and in this review a special focus was therefore set on what is known about an ineffective T cell response. Myeloid-derived suppressor cells (MDSCs), anti-inflammatory macrophages, regulatory T cells (Tregs) as well as osteoclasts all suppress immune defense mechanisms and negatively regulate T cell-mediated immunity. Thus, these cells are considered to be potential targets for immune therapy. The success of immune checkpoint inhibition in cancer treatment encourages the transfer of such immunological approaches into treatment strategies of other chronic diseases. Here, we discuss whether immune modulation can be a therapeutic tool for the treatment of chronic implant-related bone infections.